Relationship between Bilingual Experience and Cognitive Control of Bilingual Children - Xiaowei GONG; Aslı AKTAN-ERCİYES; Dilay Z. KARADÖLLER (Dilbilim Araştırmaları Dergisi, 2024)
There has been growing interest in how different dimensions of bilingual experience relate to cognitive abilities within the bilingual group. However, this interest rarely targeted data from young bilingual children who lack sufficient language production. The current study includes a variety of bilingual experience-related factors, such as language proficiency, language use, and code-switching frequency, to investigate 30- to 48-month-old bilingual children as well as their parents. Results showed that children’s age, rather than any of the bilingual-experience-related variables from neither children nor parents, predicted children’s cognitive control abilities. This study is one of the few that looked at the bilingual effects by including three bilingual-experience- related dimensions as well as parental factors. The implications of applying the bilingual experience dimension-based approach and including environmental factors while studying young bilingual age groups with limited language production were discussed.